Analisis Not in Employment, Education or Training (NEET) pada Penduduk Usia Muda di Kawasan Timur Indonesia Tahun 2022 dengan Regresi Logistik Biner Tiga Level - Amaliah, Rizka; Sitorus, Jeffry Raja Hamonangan (Seminar Nasional Official Statistics, 2024)
NEET is one of youth issue that can impact development, because its crucial role in national development. The NEET problem in Eastern Part of Indonesia (KTI) is higher than Western Part of Indonesia (KBI), in line with KTI’s lagging development. Studying NEET requires consideration from various aspects, because of varying NEET across regencies/cities. Additionally, youth career decisions can be influenced by family background and individual characteristics. This study aims to analyze the factors causing young people in KTI becomes NEET in 2022 using multilevel binary logistic regression, consisting of individual, household, and regencies/cities levels. Data sources include Sakernas August 2022, PODES 2021, BPS Provincial Publications in Numbers 2023, and Provincial Welfare Statistics 2022. The study found that NEET status in KTI is influenced by gender, migration status, disability, household head’s gender, household head’s education level, household head’s employment status, employment opportunities, and the ratio of high schools per 100 km².